Representing Joint Rule as the Murshid-i Kāmil's Will: Consensus-based Decision-making in Early Safavid Iran. (October 2016) - Trausch, Tilmann
At first glance, early Safavid Iran may not be the ideal place to search for forms of consensual rule in the early modern Persianate world, as there where neither estates nor institutionalised procedures for consens-us-based decision-making. However, perhaps it is no less suitable for such considerations than any other non-European realm. As with most other contemporary or present-day rulers, the early Safavids claim for absolute power was rather convention than reality, a fact that is well reflected in present-day scientific literature. However, this is not the case for 'rule by consensus'. Was consensus and consensus-based decision-making an issue in 16 th -century Iran? If we look at the reports of the chronicles from the Safavids courtly sphere on their first ruler, Ismaʿil, we find passages that might well be read that way. Although it is somewhat difficult to imagine Ismaʿil thinking in terms of consensus or even mutual benefit, maybe he did just that. Obviously, 'rule by consensus' is a topic from Medieval Studies and is strongly based on the realms of medieval Europe, with no equivalents to many of the specific phenomena, procedures and theories elsewhere. While a 'rule by consensus' did not exist in early Safavid Iran, consensus-based decision-making did.